Future changes of socioeconomic exposure to potential landslide hazards over mainland China - Donghuan Li; Youcun Qi; Tianjun Zhou; Wenxia Zhang (Weather and Climate Extremes)
Landslides are among the most destructive natural disasters, having huge socioeconomic impacts. Here, we investigate future changes in potential rainfall-induced landslide activities and their socioeconomic consequences in mainland China using CMIP6 simulations under five combined scenarios of the Shared Socioeconomic Pathways and the Representative Concentration Pathways (SSP1-1.9, SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5). The potential landslide activities over mainland China are projected to increase over the 21st century. The regional mean increases over mainland China under the SSP1-1.9, SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5 scenarios, at the end of the 21st century, are approximately 20.6%, 24.8%, 27.2%, 33.1%, and 46.5%, respectively, compared to present day. Population exposure to potential landslide hazards is projected to increase under SSP2-4.5, SSP3-7.0, and SSP5-8.5 scenarios, but decline under SSP1-1.9 and SSP1-2.6 scenarios due to population reduction. Meanwhile, economic exposure is expected to rise substantially across mainland China due to the greatly increased GDP. In general, the most populous and economically developed southern China will experience the largest socioeconomic exposure percentage increase among the subregions due to the joint influence of climate change and socioeconomic change. Compared with SSP1-1.9 scenario, the higher emission levels of SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5 will result in 20.4%, 32.0%, 60.6%, and 125.8% more increases in potential landslide days and 16.2%, 42.9%, 80.3%, and 4.6% less increases in anti-risk capacity (ability to resist landslide risk) in mainland China, respectively, at the end of the 21st century. The southern Tibetan Plateau is projected to experience greater increases in landslide days and decreases in anti-risk capacity than other subregions, if high emission scenarios are selected over SSP1-1.9.